Isomer-specific analysis of chlorinated biphenyls, naphthalenes and dibenzofurans in Delor: polychlorinated biphenyl preparations from the former Czechoslovakia - Taniyasu, Sachi; Kannan, Kurunthachalam; Holoubek, Ivan; Ansorgova, Alena; Horii, Yuichi; Hanari, Nobuyasu; Yamashita, Nobuyoshi; Aldous, Kenneth M (Environmental pollution (Barking, Essex, 2003)
Technical polychlorinated byphenyl (PCB) preparations--Delors 103, 104, 105, and 106--produced in the former Czechoslovakia were analyzed for their chlorobiphenyl (CB), chloronaphthalene (PCN) and chlorinated dibenzofuran (PCDF) composition and content using high resolution gas chromatography-mass spectrometry techniques. The congener patterns of Delors 103, 104, 105, and 106 resembled Aroclors 1242, 1248, 1254, and 1260. Delors contained PCNs and PCDFs, as impurities, at microgram per gram concentrations. Concentrations of PCNs and PCDFs in Delors were greater than those found in the corresponding Aroclors. The potential for the emissions of PCNs and PCDFs from Delor was estimated to be 3680 and 860 kg, respectively. Non- and mono-ortho PCBs were the major contributors to 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) equivalents in Delor mixtures.
Keywords: Czech Republic; látky znečišťující životní prostředí; Gas Chromatography-Mass Spectrometry; Naphthalenes; plynová chromatografie s hmotnostně spektrometrickou detekcí; naftaleny; isomerie; Benzofurans; benzofurany; Environmental Pollutants; Isomerism; Polychlorinated Biphenyls; Česká republika; polychlorované bifenyly